MTA1‐mediated RNA m6A modification regulates autophagy and is required for infection of the rice blast fungus. Issue 1 (13th April 2022) - Ren, Zhiyong; Tang, Bozeng; Xing, Junjie; Liu, Caiyun; Cai, Xuan; Hendy, Ahmed; Kamran, Muhammad; Liu, Hao; Zheng, Lu; Huang, Junbing; Chen, Xiao‐Lin
Summary: In eukaryotes, N 6 ‐methyladenosine (m 6 A) is abundant on mRNA, and plays key roles in the regulation of RNA function. However, the roles and regulatory mechanisms of m 6 A in phytopathogenic fungi are still largely unknown. Combined with biochemical analysis, MeRIP‐seq and RNA‐seq methods, as well as biological analysis, we showed that Magnaporthe oryzae MTA1 gene is an orthologue of human METTL4, which is involved in m 6 A modification and plays a critical role in autophagy for fungal infection. The Δ mta1 mutant showed reduced virulence due to blockage of appressorial penetration and invasive growth. Moreover, the autophagy process was severely disordered in the mutant. MeRIP‐seq identified 659 hypomethylated m 6 A peaks covering 595 mRNAs in Δ mta1 appressoria, 114 m 6 A peaks was negatively related to mRNA abundance, including several ATG gene transcripts. Typically, the mRNA abundance of MoATG8 was also increased in the single m 6 A site mutant ∆ atg8 / MoATG8 A982C, leading to an autophagy disorder. Our findings reveal the functional importance of the m 6 A methylation in infection of M. oryzae and provide novel insight into the regulatory mechanisms of plant pathogenic fungi.